Integrating evolutionary and regulatory information with a multispecies approach implicates genes and pathways in obsessive-compulsive disorder. Issue 1 (December 2017) - Noh, Hyun; Tang, Ruqi; Flannick, Jason; O'Dushlaine, Colm; Swofford, Ross; Howrigan, Daniel; Genereux, Diane; Johnson, Jeremy; Grootheest, Gerard; Grünblatt, Edna; Andersson, Erik; Djurfeldt, Diana; et al.
Abstract Obsessive-compulsive disorder is a severe psychiatric disorder linked to abnormalities in glutamate signaling and the cortico-striatal circuit. We sequenced coding and regulatory elements for 608 genes potentially involved in obsessive-compulsive disorder in human, dog, and mouse. Using a new method that prioritizes likely functional variants, we compared 592 cases to 560 controls and found four strongly associated genes, validated in a larger cohort.NRXN1 andHTR2A are enriched for coding variants altering postsynaptic protein-binding domains.CTTNBP2 (synapse maintenance) andREEP3 (vesicle trafficking) are enriched for regulatory variants, of which at least six (35%) alter transcription factor-DNA binding in neuroblastoma cells.NRXN1 achieves genome-wide significance (p  = 6.37 × 10−11 ) when we include 33, 370 population-matched controls. Our findings suggest synaptic adhesion as a key component in compulsive behaviors, and show that targeted sequencing plus functional annotation can identify potentially causative variants, even when genomic data are limited. Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder with symptoms including intrusive thoughts and time-consuming repetitive behaviors. Here Noh and colleagues identify genes enriched for functional variants associated with increased risk of OCD.